PENGARUH BUDAYA SEKOLAH DAN DUKUNGAN ORANGTUA TERHADAP PRESTASI BELAJAR MATA PELAJARAN IPS SISWA KELAS VII DI SMP NEGERI 2 KOTA PROBOLINGGO - Paulina Christiani (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2016)
This study aims to know the influence of school culture and encouragement from parents toward learning achievement of social subject of seventh graders at SMP Negeri 2 Probolinggo. The respondents of this study were sixty eight students. As the results, school culture and encouragement from parents influence positively toward socal learning achievement.